Earthquake Risk and Preparedness in Bangladesh: The Indispensable Role of Rehabilitation Medicine (KYAMC Journal, 2026)
Background: Bangladesh is located within a seismically active region influenced by the interactions of the Indian, Eurasian, and Burmese tectonic plates, making the country vulnerable to potentially damaging earthquakes. Despite this geological risk, earthquake preparedness in Bangladesh has historically received limited attention, largely due to the country’s greater exposure to floods and cyclones and the absence of a catastrophic earthquake in recent decades. This relative seismic quiescence has contributed to low public risk perception and inadequate prioritization of earthquake-specific preparedness. In contrast, neighboring South Asian countries have experienced multiple devastating earthquakes, resulting in substantial mortality and a high burden of long-term disability.Materials and Methods: This article is a narrative review synthesizing existing evidence on earthquake risk and preparedness in Bangladesh, with emphasis on the role of Rehabilitation Medicine in disaster management. Relevant literature was identified through searches of PubMed, Google Scholar, and selected grey literature from national and international disaster management and health agencies. Search terms included earthquake, Bangladesh, South Asia, disaster preparedness, rehabilitation, and physiatry. Sources were selected based on relevance to seismic risk, injury patterns, rehabilitation needs, and disaster rehabilitation models, and findings were synthesized thematically. Formal systematic review procedures were not applied.Results: Evidence from South Asia consistently demonstrates that earthquakes result in significant long-term disability, predominantly due to musculoskeletal trauma, spinal cord injuries, and neurological impairments. However, current preparedness frameworks in Bangladesh insufficiently integrate rehabilitation services, workforce planning, and continuity of care across the disaster management continuum.Conclusion: Rehabilitation must be recognized as a core component of earthquake preparedness in Bangladesh. Systematic integration of physiatrist-led rehabilitation teams within disaster management systems is essential to reduce long-term disability, optimize functional outcomes, and strengthen national health system resilience against future seismic events.